5b-3=2b

Simple and best practice solution for 5b-3=2b equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5b-3=2b equation:



5b-3=2b
We move all terms to the left:
5b-3-(2b)=0
We add all the numbers together, and all the variables
3b-3=0
We move all terms containing b to the left, all other terms to the right
3b=3
b=3/3
b=1

See similar equations:

| -25y+13=38 | | E^(3x)-6=150 | | -3x+53+11x+21=90 | | 10(g-86)=8 | | 6y=30-12 | | 2t-5=t-2 | | b^2+28b-27=23 | | -8y-20=4 | | 16x-16=90 | | y=-2(1)^2-4(1) | | 2b+1=3b | | y=-2(1)^2-4(1 | | 2(x+7)-7=7 | | 16x-16+4x+26=90 | | 1=x-x^2 | | q^2-2q=15 | | 20y-30=20 | | 7w-6=4 | | 6y+9=15 | | 4=s+2 | | 10=2p/12 | | (14x-22)+(5+55)=90 | | 3x-7=16-2x | | 7x+2=20+x | | -2z+3+z=-12 | | x^2-25x-129=3 | | y=8.55+20 | | 20x-42=6x | | 3w=6w-45 | | h^2-18h=-20 | | 6^-3n=6^3n-1 | | -3.4x-0.3=1.4 |

Equations solver categories